PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI DENPASAR - Esa Widhiarta, I Gede Teguh; Wardana, Made (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
The purpose of this study was to determine the effect of brand awareness, perceived quality, brand associations, and brand loyalty to the purchasing decision iphone in Denpasar. This study used a qualitative research using surveys and questionnaires to 120 respondents. The data analysis technique used in this study is multiple regression. It was found that brand awareness has positive influence on purchasing decisions. Perceived quality positive influence on purchasing decisions. Positive effect on the brand association purchase decision. Finally, the positive effect of brand loyalty on purchase decisions.
Keywords: Ekuitas Merek; Keputusan Pembelian